Allyl methyl trisulfide protected against LPS-induced acute lung injury in mice via inhibition of the NF-κB and MAPK pathways - Wang, Shuo; Liu, Jinqian; Dong, Jing; Fan, Zongqiang; Wang, Fugui; Wu, Ping; Li, Xiaojing; Kou, Ruirui; Chen, Fang (Frontiers in Pharmacology, 2022)
Allyl methyl trisulfide (AMTS) is one major lipid-soluble organosulfur compound of garlic. Previous studies have reported the potential therapeutic effect of garlic on acute lung injury (ALI) or its severe condition acute respiratory distress syndrome (ARDS), but the specific substances that exert the regulatory effects are still unclear. In this study, we investigate the protective effects of AMTS on lipopolysaccharide (LPS)-induced ALI mice and explored the underlying mechanisms. In in vivo experiments, ICR mice were pretreated with 25-100 mg/kg AMTS for 7 days and followed by intratracheal instillation of LPS (1.5 mg/kg). The results showed that AMTS significantly attenuated LPS-induced deterioration of lung pathology, demonstrated by ameliorative edema and protein leakage, and improved pulmonary histopathological morphology. Meanwhile, the expression of inflammatory mediators and the infiltration of inflammation-regulation cells induced by LPS were also inhibited. In vitro experiments also revealed that AMTS could alleviate inflammation response and inhibit the exaggeration of macrophage M1 polarization in LPS-induced RAW264.7 cells. Mechanistically, we identified that AMTS treatment could attenuate the LPS-induced elevation of protein expression of p-IκBα, nuclear NF-κB-p65, COX2, iNOS, p-P38, p-ERK1/2, and p-JNK. Collectively, these data suggest that AMTS could attenuate LPS-induced ALI and the molecular mechanisms should be related to the suppression of the NF-κB and MAPKs pathways.